2008
DOI: 10.1007/s12052-008-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

What Conceptions do Greek School Students Form about Biological Evolution?

Abstract: In Greece, since 2000, the teaching of evolutionary theory is restricted solely to lower (junior) high school and specifically to ninth grade. Even though the theory of evolution is included to the 12th grade biology textbook, it is not taught in Greek upper (senior) high schools. This study presents research conducted on the conceptions of Greek students regarding issues set out in the theory of evolution after the formal completion of the teaching of the theory. The sample comprised 411 10th grade students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
17
0
3
Order By: Relevance
“…Nota bene, that this is the first time that such a study has been carried out in our country. Previous studies done in Greece were researching the various factors that influence the teaching of the evolutionary theory only in secondary education (Prinou et al 2008).…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nota bene, that this is the first time that such a study has been carried out in our country. Previous studies done in Greece were researching the various factors that influence the teaching of the evolutionary theory only in secondary education (Prinou et al 2008).…”
Section: Research Questionmentioning
confidence: 99%
“…The misconceptions are called "Lamarckian" because "organisms can develop new adaptive characteristics in response to environmental demands -which is-a Lamarckian principle" (Samarapungavan & Wiers 1997, p. 148) 1 . Related research done in Greece (Prinou et al 2008) has shown that even though pupils accepted biological evolution, they did not use the concept of natural selection in their explanations, but invoked pre-Darwinian explanations instead, which referred to those described by Mayr (1991;2001). The pupils-despite the fact that they had been taught the theory of evolution ostensibly in the ninth grade-treated organisms as a unified total of almost identical individuals which acquire new traits in order to deal with the needs of the environment.…”
Section: Introduction -Literature Reviewmentioning
confidence: 99%
“…People holding this misconception often also believe that the organisms change because they need to (for example, 60% in the Prinou et al study and 36% in the Yates and Marek study), in order to survive changing environmental conditions (59% in the Prinou et al study). Prinou et al (2008) found a statistically significant correlation between the misconceptions that organisms adapt because they need to survive, and organisms adapting to their environments. The inference is that if one holds an alternative framework (a broad way of thinking about a topic), many of the individual misconceptions associated with that framework will also be present.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the incorrect idea that individual organisms evolve was found in about a fifth of the studies reviewed, held by varying percentages of the samples. In two of the large studies it was held by 47% of the pupils (Prinou et al 2008) and 77% of the post-tuition sample (Yates and Marek 2014). People holding this misconception often also believe that the organisms change because they need to (for example, 60% in the Prinou et al study and 36% in the Yates and Marek study), in order to survive changing environmental conditions (59% in the Prinou et al study).…”
Section: Discussionmentioning
confidence: 99%
“…Here, an organism is wrongly seen as being able to address problems it can face in the environment, by altering itself in such a way that can be passed onto its offspring. Variations on this incorrect definition of adaptation are recorded at many educational levels in many countries (Bizzo 1994;Enzel Clough & Wood-Robinson 1985;Ferrari & Chi 1998;Geraedts & Boersma 2006;Gregory 2009;Kampourakis & Zogza 2008, 2009Nehm & Reilly 2007;Palmer 1996;Prinou et al 2008;Settlage 1994;Tidon & Lewontin 2004;Zuzovsky 1994). At the same time, students have problems differentiating between the noun and verb versions of the word 'adaptation' (Lucas 1971;van Dijk & Reydon 2010), meaning that careful use of language is important in teaching evolution (Alters & Nelson 2002;Smith et al 1995;Tidon & Lewontin 2004).…”
Section: Introductionmentioning
confidence: 99%